Development and manufacturing fixing holder and gearing mechanism for a electrical go-kart - Mohamed Samud, Nur Adlin Farhana; Mohd Yusof, Ab Aziz; Ismail, Ainaa Maya Munira (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This project focuses on designing and fabricating a go-kart motor fixing holder and gearing system to enhance stability and efficiency in electric go karts. The development process involved conceptualizing three initial designs and refining and finalizing the most suitable concept using SolidWorks software. The fabrication phase, which spanned approximately 12 weeks, incorporated essential manufacturing processes such as cutting, drilling, welding, and bending to construct the motor fixing holder and gearing system. The motor fixing holder was fabricated using 2mm thick recycled steel plates, while the gearing system was assembled with a 3mm steel driven gear welded onto the motor shaft. A relay based starter circuit was integrated to ensure a safe and controlled power transfer, preventing accidental motor engagement. The final prototype was successfully manufactured and assembled, demonstrating practical functionality in securing the motor and transmitting power efficiently to the wheels. The results confirm that the fabricated system meets the intended design objectives, providing a secure mounting solution and reliable gearing mechanism for the go-kart. Future improvements can be made by optimizing material selection, enhancing structural reinforcement, and refining the gearing system to improve performance, durability, and overall efficiency.